Content Of Processed Catfish (Clarias Batrachus ) On Nutritional Status - fatmawati, nurul; Zulfiana, Yezvi; Soekmawaty Riezqy Ariendha, Dian (STIKES Yarsi Mataram, 2024)
The nutritional problem in Indonesia is still a fairly large and increasingly complex problem. One effort that can be made is to adopt a healthy lifestyle, including a balanced diet, which is one of the main factors causing complex nutritional problems in Indonesia. PSG data in 2017, the prevalence of stunting in NTB Province was 37.2%, higher than the national average, namely 29.6%. This figure also increased compared to 2016, namely 29.9% or an increase of 7.29%. %. Catfish (Clarias Batrachus). Catfish is a type of freshwater fish that is very popular with the public. Catfish is a commodity with important economic value and is widespread in Indonesia. The nutritional content of catfish contains 76.0% water, 17.7% protein, 4.8% fat and 0.3% carbohydrates and 1.2% minerals. The aim of this research is to determine the nutritional status of processed catfish. The research method is a literature review, which is trying to explore the content of processed catfish on nutritional status. The results of a review of 5 journals show that processed catfish contains protein, calories, fat, carbohydrates, water and minerals which play an important role in nutritional status. compared to 2016, namely 29.9% or an increase of 7.29%. %. Catfish (Clarias Batrachus). Catfish is a type of freshwater fish that is very popular with the public. Catfish is a commodity with important economic value and is widespread in Indonesia. The nutritional content of catfish contains 76.0% water, 17.7% protein, 4.8% fat and 0.3% carbohydrates and 1.2% minerals. The aim of this research is to determine the nutritional status of processed catfish. The research method is a literature review, which is trying to explore the content of processed catfish on nutritional status. The results of a review of 5 journals show that processed catfish contains protein, calories, fat, carbohydrates, water and minerals which play an important role in nutritional status.